The process of trace metals enrichment in pyrite under methane seepage in the northern South China Sea - Ling, Yanting; Chen, Xuan; Wu, Daidai; Zhang, Qinyi; Mao, Shengyi; Jin, Guangrong; Liu, Jie; Zhai, Haizhen; Yang, Chao; Su, Zheng; Wu, Nengyou (Frontiers in Marine Science, 2025)
Pyrite is an important indicator of methane seepage. The effects of organic sulfate reduction (OSR) and sulfate-driven anaerobic oxidation of methane (SD-AOM) on the trace metals in pyrite have aroused interest; however, further studies about how these two pathways control the trace element patterns are still required. Therefore, we studied the geochemical and mineralogical characteristics of sediment samples from the northern South China Sea, aiming to investigate the enrichment mechanisms of trace elements into pyrites in methane seep systems. We applied laser ablation–inductively coupled plasma–mass spectrometry (LA-ICP-MS) to analyze the trace element patterns of pyrites in core Z22–3. We used Sr/Ca-Mg/Ca, (Mo/U) EF values, chromium reducible sulfur (CRS) content, total organic carbon (TOC), δ34S, and δ13C values of bulk sediments to determine the position of sulfate–methane transition zones (SMTZs). Progressively more positive δ34S values (up to −36.54‰) of the CRS and an increase in Mg/Ca indicate the enhancement of SD-AOM, suggesting that the position of SMTZs is located at depths of 181 to 481 and 1,101 to 1,401 cmbsf. Within SMTZs, pyrites exhibit obvious enrichments in Co, Ni, Mo, and Pb and depletion in Mn, Zn, Cu, and V. We discuss the process of methane seepage affecting trace elements in pyrites: the reductive dissolution of iron/manganese oxyhydroxide aggregates fueled by the enhancement of AOM and substitution for ferrous in pyrites contribute to the enrichments of Mo, Co and Ni in pyrites. Elements with faster water exchange kinetics rates than Fe, such as Cu, Pb and Zn, rather precipitate as independent metal sulfides than incorporating into pyrite, thus resulting in the depletion of these trace elements in pyrites. This study provides novel insight into the deep-sea trace element cycle between sediments and authigenic pyrites, establishing geochemical indicators of AOM based on trace element patterns in pyrites.